Wheat Straw Return Influences Nitrogen-Cycling and Pathogen Associated Soil Microbiota in a Wheat–Soybean Rotation System - Yang, Hongjun; Ma, Jiaxin; Rong, Zhenyang; Zeng, Dandan; Wang, Yuanchao; Hu, Shuijin; Ye, Wenwu; Zheng, Xiaobo (Frontiers in Microbiology, 2019)
Returning straw to soil is an effective way to sustain or improve soil quality and crop yields. However, a robust understanding of the impact of straw return on the composition of the soil microbial communities under field conditions has remained elusive. In this study, we characterized the effects of wheat straw return on soil bacterial and fungal communities in a wheat–soybean rotation system over a 3-yr period, using Illumina-based 16S rRNA and internal transcribed region (ITS) amplicon sequencing. Wheat straw return significantly affected the -diversity of the soil bacterial, but not fungal, community. It enhanced the relative abundance of the bacterial phylum Proteobacteria and the fungal phylum Zygomycota, but reduced that of the bacterial phylum Acidobacteria and the fungal phylum Ascomycota. Notably, it enriched the relative abundance of nitrogen-cycling bacterial genera such as Bradyrhizobium and Rhizobium. Analysis of soil chemical properties indicated that straw return soils had significantly higher total nitrogen contents than no straw return soils. In addition, the relative abundance of fungal genera containing pathogens was significantly lower in straw return soils relative to control soils, such as Fusarium, Alternaria, and Myrothecium. These results suggested a selection effect from the three-year continuous straw return treatment and the soil bacterial and fungal communities were moderately changed.